Innentitelbild: Strukturelle und mechanistische Studien zur Substrat‐ und Stereoselektivität der Indol‐Monooxygenase VpIndA1: Neue Wege für biokatalytische Epoxidationen und Sulfoxidationen (Angew. Chem. 17/2023). (15th March 2023) - Kratky, Julia; Eggerichs, Daniel; Heine, Thomas; Hofmann, Sarah; Sowa, Philipp; Weiße, Renato H.; Tischler, Dirk; Sträter, Norbert
Abstract : A flavin‐dependent group E monooxygenase ("GEM") has been characterized by crystal‐structure analysis, computational and kinetic studies to reveal substrate binding and mechanistic details for this class of enzymes for the first time. Based on these data, Dirk Tischler, Norbert Sträter, and co‐workers redesigned the substrate binding pocket to synthesize chiral epoxides and sulfoxides with high stereoselectivity, a true treasure of molecular gems, as described in their Research Article (e202300657) .